Exploring the Association between Parental Factors and Age of Onset of Alcohol and Tobacco's Using - Zhuo Li TAO; Yi LIU (Tehran University of Medical Sciences, 2018)
Background: There are few reports about relationship between parents' age of onset of substance use and their children's age of onset. The aim of this study was to explore the association between parents' age of onset of substance use and that of their children, the influence of parents' factor on their children's age of onset of substance use. Methods: Overall, 2036 Chinese college students from ten universities in five cities were assessed for their alcohol and tobacco's use, and they reported on their parents' alcohol and tobacco's use, their parents' attitudes towards their substance use and their parental education level. Among current substance users, multiple regression analyses were used to test whether their parents' age of onset of substance use and their parents' attitudes towards their substance use predict their age of onset of substance use. Results: Parents of children who used substances earlier showed significantly more tolerance towards their children's substance use than parents of children with a later onset of substance use. Among current substance users, their parents' age of onset of substance significantly predicted children's age of onset. The parents' attitudes had a significant impact on their children's age of onset of substance use. Conclusion: Parental factors (attitudes towards their children's substance use and parents' age of onset of substance use) are related to age of onset and substance use in children. Prevention program for parents is necessary, especially for those parents who have a tolerant attitude towards their children's substance use.